SQL fundamentals - Jones, Arie D. (LiveLessons., 2009)
Start building powerful SQL queries right now! 8 Hours of Expert Video Instruction This one-of-a-kind video package gives you instant skills, answers, and solutions from eight hours of quick, easy DVD video LiveLessons. Database expert Arie Jones teaches you SQL the right way ... hands-on, and step-by-step! These video lessons focus on exactly what you need to know to master new skills fast and put them to work immediately. Simply place the DVD video in your computer's DVD drive, and begin mastering SQL the easy way! Watch and learn how to write queries using the world's #1 open source database, MySQL--and build skills you can use with any database, from Oracle to SQL Server! Learn to navigate MySQL's command line and Query Browser ... get data out of databases with SELECT ... sequence results with ORDER ... filter data with WHERE ... manage, aggregate, and group data ... work with tables ... manage security and access ... even use advanced functions, views, and stored procedures! For even more practical guidance, turn to Sams Teach Yourself SQL in 24 Hours, Fourth Edition, by Ryan Stephens, Ron Plew, and Arie Jones. With 24 easy, practical, hands-on lessons, it's the only SQL book you'll ever need!